The Book of Tobit: Texts from the Principal Ancient and Medieval Traditions. With Synopsis, Concordances, and Annotated Texts in Aramaic, Hebrew, Greek, Latin, and Syriac - Gathercole, Simon J.; Stuckenbruck, Loren T.; Weeks, Stuart (Fontes et Subsidia ad Bibliam pertinentes, 2004)
Biographical note: Simon Gathercole is Lecturer in New Testament at the University of Aberdeen. Loren Stuckenbruck is Westcott Professor of Biblical Studies at the University of Durham. Stuart Weeks is Lecturer in Old Testament at the University of Durham.